Can concurrent use of king vision video laryngoscope and fiberoptic bronchoscope improve efficacy and safety of awake intubation in patients with limited mouth opening? - A case report - Gupta, Sunana; Gupta, Rahul; Mehta , Nandita; Saini, Heena (Asian Journal of Medical Sciences, 2024)
Securing the airway by endotracheal intubation in a patient with a restrictive mouth opening poses a challenge to anesthesiologists. Awake tracheal intubation using flexible fiberoptic bronchoscopy is the gold standard in the anesthetic management of patients with restricted mouth openings. Awake video laryngoscopy (VL) is being increasingly used for the management of the anticipated difficult airways. We report a case of temporomandibular joint ankylosis with restrictive mouth opening posted for laparoscopic nephrectomy managed by awake intubation with the combined use of king vision VL (KVVL) and fiberoptic bronchoscope (FOB). KVVL provided an improved and clear view of the airway structures and FOB helped in guiding and maneuvering the tube safely into the larynx. The combined use of KVVL and FOB enhanced the effectiveness and safety of the procedure.